2020
DOI: 10.1042/cs20190995
|View full text |Cite
|
Sign up to set email alerts
|

A protective role of renalase in diabetic nephropathy

Abstract: Renalase, a recently discovered secreted flavoprotein, exerts anti-apoptotic and anti-inflammatory effects against renal injury in acute and chronic animal models. However, whether Renalase elicits similar effects in the development of diabetic nephropathy (DN) remains unclear. The studies presented here tested the hypothesis that Renalase may play a key role in the development of DN and may have therapeutic potential for DN. Renalase expression was measured in human kidney biopsies with DN and in kidneys of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…These symptoms were ameliorated with renalase overexpression in db/db mice. Renalase exerted the protective effects in DN through inhibition of mesangial cell hypertrophy, oxidative stress, and inflammation [ 35 ]. The results of the molecular studies also showed a linkage between the renalase gene polymorphisms and kidney diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms were ameliorated with renalase overexpression in db/db mice. Renalase exerted the protective effects in DN through inhibition of mesangial cell hypertrophy, oxidative stress, and inflammation [ 35 ]. The results of the molecular studies also showed a linkage between the renalase gene polymorphisms and kidney diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the pivotal underlying mechanisms of myocardial fibrosis validated by the fibroblast-specific, in vivo model ( 7 ), the particular focus herein is on the TGF-β and mitogen-activated kinases (MAPKs) pathways, which are evidenced targets by renalase ( 11 , 13 , 16 , 17 , 21 , 68 , 69 ), as presented in Figure 1 .…”
Section: The Identification Of Renalase As a Relevant Antifibrotic Mo...mentioning
confidence: 99%
“…Its N-terminal peptide, by binding to the calcium-transporting ATPase PMCA4b, activates the PI3K/AKT and MAPK pathways. In patients with chronic kidney disease, renalase could reduce the expression of mediators involved in the inflammatory response and glomerular fibrosis, such as pro-inflammatory cytokines and NADPH oxidase [ 9 ]. Recombinant renalase diminishes glomerular hypertrophy, interstitial fibrosis, proteinuria, hypertension and myocardial remodeling by decreasing the phosphorylation of ERK-1/2 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic kidney disease, renalase could reduce the expression of mediators involved in the inflammatory response and glomerular fibrosis, such as pro-inflammatory cytokines and NADPH oxidase [ 9 ]. Recombinant renalase diminishes glomerular hypertrophy, interstitial fibrosis, proteinuria, hypertension and myocardial remodeling by decreasing the phosphorylation of ERK-1/2 [ 9 ]. It has been shown that renalase may also protect against cisplatin and hydrogen peroxide-induced toxic injury of proximal tubular (HK-2) cells [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%